The Effect of Music Therapy on Pain Level in Infusion in Children 6-12 Years of Age at Arga Makmur Hospital - Rita Lestari (ANJANI Journal (Medical Science & Healthcare Studies), 2021)
Introductions: Infusion is an invasive medical procedure that is often performed and causes acute pain and fear in children (Silkorova Hrazdilova, 2011). Non-pharmacological pain management can be done through distraction, one of which is music therapy (Baulch, 2010). There are still many complaints of pain during the infusion procedure at Arga Makmur Hospital. to determine the effect of music therapy on the pain level of infusion in children aged 6-12 years in the Melati  room of Arga Makmur Hospital. Method: This type of research is a quasi-experimental research design with a two-group research design, namely in the study there were two groups randomly selected. The first group was treated and the other group was not treated. (Sugiono, 2013). Sampling by accidental sampling, a large sample of 10 people were given trapi music 10 people were not given music traps. Data were analyzed univariately and bivariately displayed in the form of a frequency distribution table. The results: of the study the average pain level of patients who were not given music therapy was 7.70 the pain level of patients who were given music therapy was 5.80. The results of the Shapiro Wilk test p value 0.05 and the paried statistical test sample t test p value 0.000, There is an effect of the effect of music therapy on the pain level of the infusion in children aged 6-12 years in the Melati room of Arga Makmur Hospital. The results of the study were to improve overall health services, especially regarding non-pharmacological pain intensity management, namely music therapy. Conclusions It is hoped that it can add knowledge and insight for nurses in distraction techniques to pain intensity.